2016
DOI: 10.1177/0300060516662134
|View full text |Cite
|
Sign up to set email alerts
|

Alleviated negative rather than positive attentional bias in patients with depression in remission: an eye-tracking study

Abstract: ObjectiveTo investigate attentional bias toward happy and sad faces in remitted depressed (RD) patients compared with healthy control (HC) subjects.MethodsThis cross-sectional study enrolled RD patients and sex- and age-matched HC subjects. Eye movement data were acquired for all study participants while free viewing a 2 × 2 matrix of emotional faces. The attentional bias toward different emotional faces and whether the attention maintenance components generated attentional bias in the RD patients were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…Symptom severity has been found to correlate both with an attentional bias for sad and happy faces (Duque and Vazquez, 2015). Some studies report a persisting attentional bias to sad faces in remitted MD (Soltani et al, 2015), while others found no significant difference as compared to controls concerning sad faces, but a decreased attentional bias toward happy faces (Li et al, 2016a). …”
Section: Discussionmentioning
confidence: 99%
“…Symptom severity has been found to correlate both with an attentional bias for sad and happy faces (Duque and Vazquez, 2015). Some studies report a persisting attentional bias to sad faces in remitted MD (Soltani et al, 2015), while others found no significant difference as compared to controls concerning sad faces, but a decreased attentional bias toward happy faces (Li et al, 2016a). …”
Section: Discussionmentioning
confidence: 99%
“…Siegle et al [71] reported faster pupillary responses in non-depressed individuals to positive rather than negative stimuli. In contrast, depressed persons displayed slower pupil dilation responses to positive stimuli in conditions associated with reduced cognitive load (see also [72], [73], [74], [75], [76], [77]). More recently Price et al [78] investigated attentional bias, including pupil bias and diameter, to predict depression symptoms over a two year follow up period in a sample of adolescents displaying high ratings of anxiety.…”
Section: Nonverbal Signs For Depression Assessmentmentioning
confidence: 99%
“…They captured their pupils' adaptation modes in continuous stages of darkness and light and explored the quantitative measuring method of autism. Typical applications of eye movement information in the diagnosis of depression were described in paper [11][12][13][14]. Shengfu Lu et al had patients with major depressive disorder (MDD) and nondepressed controls complete eye-tracking tasks and analyzed their attention preference to positive, negative, and neutral expressions [11].…”
Section: Introductionmentioning
confidence: 99%